Why Brexit Will Do Little to Change the Political Contours of the European Social Dimension - Copeland, Paul (2019)
Integration within the European social dimension, understood as the EU’s competence in the field of employment and social policy, has been fraught with obstacles. Divisions between the EU’s Member States have limited integration and resulted in a complex and piecemeal system of governance that is low down on the EU’s list of priorities. The UK is often regarded as a major obstacle limiting the scope of integration in the field and this is not without good reason. Historically, the UK has formed coalitions to block policy negotiations within the European Council and has pushed for minimal neoliberal obligations in the field. The UK’s departure from the EU could result in a step-change for the European social dimension. However, as this article will argue, the UK’s departure from the EU will do little to alter the current dominance of a neoliberal market-led ideology, as it currently transcends the political agency of the UK.